2021
DOI: 10.3390/su13169050
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Sand Drift Potential and Sand Dune Mobility over the Last Three Decades (Khartouran Erg, Sabzevar, NE Iran)

Abstract: Aeolian sediments cover about 6% of the earth’s surface, of which 97% occur in arid regions, and these sediments cover about 20% of the world’s lands. Sand drifts can harm sensitive ecosystems; therefore, this research has aimed to study wind regimes and the monitoring of sand drift potential and dune mobility in the Khartouran Erg (NE Iran). The study investigated 30 years of wind speed and direction to better understand sand dune mobility processes using the Fryberger and Tsoar methods. The results of the wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Compared to our study, dunes in Khartouran Erg (norteastern Iran) revealed similar wind performances. There, erosive winds are indicative of a low-energy environment (Rahdari and Rodríguez-Seijo, 2021) and predominantly enter from the eastern and northern directions with a directionality index ranging between 0.3 and 0.6. While wind-carried sand has a southwest trajectory, authors suggest that sand dunes have been fixed for a long time historically.…”
Section: Climate and Paleoclimate Intersectsmentioning
confidence: 99%
“…Compared to our study, dunes in Khartouran Erg (norteastern Iran) revealed similar wind performances. There, erosive winds are indicative of a low-energy environment (Rahdari and Rodríguez-Seijo, 2021) and predominantly enter from the eastern and northern directions with a directionality index ranging between 0.3 and 0.6. While wind-carried sand has a southwest trajectory, authors suggest that sand dunes have been fixed for a long time historically.…”
Section: Climate and Paleoclimate Intersectsmentioning
confidence: 99%
“…Similarly, drought and salinity are major abiotic stress factors that significantly impact the production of crops, including peanuts [18,19]. These stress factors can reduce plant growth and productivity by affecting various physiological and biochemical processes in plants [20,21]. In recent years, the identification and characterization of genes that play a crucial role in abiotic stress tolerance have become popular research topics in plant biology.…”
Section: Introductionmentioning
confidence: 99%